Pengaruh perencanaan pajak, penghindaran pajak, dan likuiditas terhadap nilai perusahaan - Hawa, Siti; Dongoran, Parlindungan; Arnisah, Siti (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The presence of business competition among companies has prompted entrepreneurs to exert greater effort in enhancing the value of their companies, with the aim of attracting investor attention and securing investments. The assessment of a company's performance by external parties is heavily influenced by its value, which serves as a reflection of its overall worth. Companies employ several strategies to enhance their value. This research employs a quantitative approach to examine the causal association and assess the influence of the independent variable on the dependent variable. The objective of this research is to examine the influence of Planning, Tax Avoidance, and Liquidity on the valuation of firms. The empirical evidence demonstrates that the variables of Tax Planning, Tax Avoidance, and Liquidity collectively exert a significant influence on Firm Value during the period spanning from 2016 to 2020. The findings indicate that tax planning has a notable beneficial impact on firm value, whereas tax avoidance has a considerable adverse effect on firm value. However, there is no significant association between liquidity and firm worth.